EDITORIAL Can We Do Better Than Scratching The Surface Of Unending Misery 2? - Dr. Mervyn Hosein (ziauddin University, 2022)
In a 1997 Editorial in the Pakistan Journal of Otolaryngology.1 I wrote, under that title, on the then emerging role of Oral and Maxillofacial Surgery (OMFS) specialization in Pakistan noting, with a degree of pride, the beneficial introductory addition of the expertise of the dento-facial specialist surgeon to the then existing group of Head and Neck surgical specialties...